P75NTR activation limits CD21lo B cell subsets expansion in response to autoimmune-inducing challenges - Cong Luo; An-Hui Zha; Ru-Yi Luo; Zhao-Lan Hu; Wei-Yun Shen; Ru-Ping Dai (iScience, 2025)
Summary: Studies, including our own, suggest that p75NTR plays a pivotal role in immune regulation. Here, we aimed to uncover the role of p75NTR signaling in regulating CD21lo B cell subsets, which are known to facilitate autoimmune activity, and to identify possible regulatory transcripts involved. Through in vitro assays, in vivo models, and RNA-seq analysis, we found that p75NTR expression and CD21lo B cell expansion were increased in B cells following TLR7/9 stimulation in vitro and in pristane-challenged mice in vivo. Interestingly, p75NTR deficiency led to a further expansion of CD21lo B cells and enhanced their pro-inflammatory characteristics. RNA-seq data revealed notable transcript alterations associated with CD21lo B cells, including increased Tbx21 expression. A potential role for p75NTR downstream signaling via phosphorylated p65 (p-p65) was also proposed. Our study provides insights into the role of p75NTR in restraining the development of CD21lo subsets and modulating autoimmune activity in response to autoimmune challenges.